Challenges and strategies of postgraduate students in online learning during the Covid-19 pandemic - Anang Fathoni; Heri Retnawati (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
The ongoing online learning during the Covid-19 pandemic has become a separate catalyst for the development of education that utilizes technology in the current industrial 4.0 era. However, on the other hand, there are still many gaps in online learning during the Covid-19 pandemic. This research study aims to (1) explore the experiences of postgraduate students in online learning; (2) describe the negative impacts and barriers to online learning, along with strategies for dealing with them; and (3) observe the potential that emerges in the future after the Covid-19 pandemic can be overcome. This research is qualitative research with a type of case study. Data were collected through open questionnaires and interviews with participants of 30 postgraduate students of the Primary education study program, Yogyakarta State University. Data analysis was accomplished by examining themes and sub-themes in each topic discussed, then determining the correlation between the sub-themes to conclude. The results show that students have varied experiences throughout online learning during the Covid-19 pandemic. In addition, students also gain negative physical and psychological impacts, get obstacles concerning data reception, gadgets, interaction with lecturers, independent study, and learning activities during the Covid-19 pandemic. However, students also still have various strategies in dealing with the obstacles and negative impacts of Covid-19. Finally, online learning during the Covid-19 pandemic is giving potential as well as negative things in the future once it is resolved.